Pengaruh Pemanfaatan Media Sosial, Kreativitas dan Modal Usaha terhadap Keberlanjutan Bisnis UMKM Milenial di Kota Medan - Anggraini, Adisty; Nawawi, Zuhrinal M (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This examination was expected to research the impact of the utilization of virtual entertainment, imagination, and business capital on the supportability of the Millennial Micro, Small and Medium Enterprises (SMEs) business in Kota Medan. All SMEs in Kota Medan were picked as the populace and 73 respondents were utilized in this examination. Information was tried through a few cycles, for example, legitimacy test, dependability tests, the exemplary supposition test as the ordinariness test, heteroscedasticity test and multicollinearity test. For testing the speculation, numerous straight relapse examination with the assistance of SPSS Statistics 20 For Windows programming. The consequences of this study show that, (1) the utilization of web-based entertainment meaningfully affects Millennial SMEs business supportability, (2) innovativeness has a positive and massive impact towards Millennial SMEs business manageability, and (3) business capital has a positive and tremendous impact towards Millennial SMEs business maintainability. Keywords: Utilization of Social Media, Creativity, Business Capital, and Business Sustainability